Literary and Sociological Approaches to the Analysis of C.B.C. English-Language Radio-Drama - Fink, Howard; Jackson, John; Nielson, Greg; Zinman, Rosalind (Culture, 1981)
This paper is an exploration of approaches to the analysis of CBC English language radio drama. Using a selected drama for illustration, we explore literary and sociological modes of analysis and the benefits derived from their combination. The objective is to develop a theoretical and methodological base for the study of radio drama as a cultural product and the relations between the structures of these works and of idea Systems within English-Canadian society. In the course of developing the analysis leads are taken for the works of Northrop Frye and Lucien Goldmann.